N = 1 trinification from dimensional reduction of N = 1, 10D E8 over SU(3)/U(1)×U(1)×Z3 and its phenomenological consequences - George Manolakos; Gregory Patellis; George Zoupanos (Physics Letters B, 2021)
We present an extension of the Standard Model that results from the dimensional reduction of the N=1, 10D E8 group over a M4×B0/Z3 space, where B0 is the nearly-Kähler manifold SU(3)/U(1)×U(1) and Z3 is a freely acting discrete group on B0. Using the Wilson flux breaking mechanism we are left in four dimensions with an N=1 SU(3)3 gauge theory. Below the unification scale we have a two Higgs doublet model in a split-like supersymmetric version of the Standard Model, which yields third generation quark and light Higgs masses within the experimental limits and predicts the LSP ∼1500GeV.